STRATEGI PEMASARAN TOKO ZOYA KEDIRI UNTUK MENINGKATKAN PEMBELIAN KONSUMEN - Prima Rizki, Shafira Putri; Ernestivita, Gesty (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This research is motivated by the interest of researchers to find out more about the marketing strategy of Toko Zoya Kediri to increase consumer purchases. The purpose of this study was to analyze the marketing strategy carried out by Zoya Kediri Stores to increase consumer purchases. This research is a field research using a qualitative approach. While this type of research is field research using primary data sources from observations and interviews with the head of the Zoya Store, Kediri and the secondary data results from the documentation. The results of the analysis show that the marketing strategy carried out by Zoya Kediri Stores to increase consumer purchases is by implementing the 4P marketing mix strategy, namely: in terms of products, Zoya Stores Kediri always innovates products, and always maintains product quality. In terms of price, namely setting prices by calculating the ratio of costs incurred and adjusted for product quality. In terms of location by choosing a strategic location, spacious and near the center of the crowd. In terms of promotion, namely doing promotions offline and online.